(untitled) (Hekima Review, 2015)
In an article sub-titled “Christian Pedagogy of Evangelization and African Ethos” published in issue 2014/1 of the Tangaza Journal of Theology and Mission, Father Gorge Kocholickal, sdb, offered what he intended to be an extensive critique of Professor Laurenti Magesa’s theology. e initiative to undertake such a review is praiseworthy, since such is rarely seen among Africanists. In the same spirit, this article is presented as a critique of Kocholickal’s review. It shows that Kocholickal’s conclusions, which are mostly negative, are based on a misreading of Magesa’s theology and, more generally, on a facile analysis of missionary realities in Africa. A focus on mission misses Magesa’s point on dialogue, a paradigmatic view of Christian spirituality impairs the ability to appreciate the speci city of its African counterpart, and a determination to clear missionaries of wrong doing sticks up nakedly at odds with documented history. For the author of this article, the praiseworthy initiative simply went wrong.